2018
DOI: 10.1038/s41467-018-04402-6
|View full text |Cite
|
Sign up to set email alerts
|

Continuous addition of progenitors forms the cardiac ventricle in zebrafish

Abstract: The vertebrate heart develops from several progenitor lineages. After early-differentiating first heart field (FHF) progenitors form the linear heart tube, late-differentiating second heart field (SHF) progenitors extend the atrium and ventricle, and form inflow and outflow tracts (IFT/OFT). However, the position and migration of late-differentiating progenitors during heart formation remains unclear. Here, we track zebrafish heart development using transgenics based on the cardiopharyngeal gene tbx1. Live ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 71 publications
(130 reference statements)
7
45
0
Order By: Relevance
“…As a universal trait, the developing heart incorporates cells from two ALPM-associated progenitor fields, the so-called first versus second heart fields (FHF and SHF, respectively) (Abu-Issa and Kirby, 2008;Meilhac et al, 2004;Stolfi et al, 2010;Tirosh-Finkel et al, 2006). While the FHF descendants set up the initial heart tube with atrium and ventricle for systemic circulation, the addition of SHF progenitors extends the heart on both poles (de Pater et al, 2009;Felker et al, 2018;Grimes and Kirby, 2009;Hami et al, 2011;Lazic and Scott, 2011;Zhou et al, 2011). As a fundamental building block of all vertebrate hearts, the interplay of FHF and SHF influences cardiac conductivity and facilitates sequential contraction (Mosimann et al, 2015); however, why two progenitor pools are required for heart formation remains uncertain.…”
Section: Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…As a universal trait, the developing heart incorporates cells from two ALPM-associated progenitor fields, the so-called first versus second heart fields (FHF and SHF, respectively) (Abu-Issa and Kirby, 2008;Meilhac et al, 2004;Stolfi et al, 2010;Tirosh-Finkel et al, 2006). While the FHF descendants set up the initial heart tube with atrium and ventricle for systemic circulation, the addition of SHF progenitors extends the heart on both poles (de Pater et al, 2009;Felker et al, 2018;Grimes and Kirby, 2009;Hami et al, 2011;Lazic and Scott, 2011;Zhou et al, 2011). As a fundamental building block of all vertebrate hearts, the interplay of FHF and SHF influences cardiac conductivity and facilitates sequential contraction (Mosimann et al, 2015); however, why two progenitor pools are required for heart formation remains uncertain.…”
Section: Heartmentioning
confidence: 99%
“…Although the nomenclature of mesodermal domains in the developing head suffers from disparities across the literature, at least part of the cardiopharyngeal field (CPF) designates an ALPMcentered progenitor pool that, in addition to forming the heart, also contributes to craniofacial and neck muscles (Diogo et al, 2015). Comparative anatomical and genetic studies across chordates have demonstrated joint cardiac and branchiomeric muscle formation, together with overlapping expression patterns in the anterior mesoderm of key regulators, including Nkx2.5, Isl1 and Tbx1 (Diogo et al, 2015;Felker et al, 2018;Gopalakrishnan et al, 2015;Heude et al, 2018;Lescroart et al, 2015;Michailovici et al, 2015;Paffett-Lugassy et al, 2017;Stolfi et al, 2010;Wang et al, 2019b). The evolutionary timeline of additional cranial muscle groups that are distinct from trunk muscle trajectories coincides with the adaption of multi-chambered hearts (Comai et al, 2019;Diogo et al, 2015;Heude et al, 2018;Theis et al, 2010).…”
Section: Craniofacial Muscle Lineagesmentioning
confidence: 99%
“…The cardiac OFT is derived from a subpopulation of cardiac progenitor cells that comprise the SHF and is the result of their continuous proliferation and addition to the primitive, linear heart tube ( Figure 2 ) [ 35 ]. Consequently, rightward looping of the elongating heart tube contributes to it acquiring a more complex structure reminiscent to the definitive heart [ 36 ] and is followed by the formation of the early chambers as the myocardium of the heart tube bulges out ( Figure 2 ) [ 37 ].…”
Section: The Right Ventricular Outflow Tractmentioning
confidence: 99%
“…Eventually, in mammals, the OFT undergoes septation, cushion formation, and rotation, giving rise to the mature structure that forms the trunk of the great arteries ( Rothenberg et al, 2003 ; Bajolle et al, 2006 ). In zebrafish, the recruitment of SHF progenitors from the anterior lateral plate mesoderm to the OFT starts around 26 hours post-fertilization (hpf) and proceeds in multiple waves ( Hami et al, 2011 ; Zhou et al, 2011 ; Jahangiri et al, 2016 ; Paffett-Lugassy et al, 2017 ; Felker et al, 2018 ). Starting at 54–56 hpf, a few immature SMCs expressing elastin appear at the arterial pole of the heart ( Grimes et al, 2006 ; Zhou et al, 2011 ; Jahangiri et al, 2016 ; Felker et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%